2017
DOI: 10.1021/acs.jnatprod.7b00301
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholinesterase Inhibitory Alkaloids from the Whole Plants of Zephyranthes carinata

Abstract: Eleven new alkaloids (1-11), classified as the 12-acetylplicamine (1), N-deformyl-seco-plicamine (2), plicamine (3-6), 4a-epi-plicamine (7), seco-plicamine (8), and lycorine (9-11) framework types, along with 15 known alkaloids (12-26) were isolated from the whole plants of Zephyranthes carinata. The structures of the new alkaloids 1-11 were established by extensive spectroscopic data interpretation. The absolute configurations of 9 and 10 were defined by single-crystal X-ray diffraction analysis. Zephycarinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 39 publications
2
12
0
Order By: Relevance
“…By changing the electrophile to MeI, the total synthesis of zephycarinatine D ( 1 b ) was accomplished in 52 % in three steps with a small amount of removable diene 14 . All the spectroscopic data were in agreement with those of the natural zephycarinatines C and D reported in the literature [2] {zephycarinatine C: []αD26= +141 ( c =0.060, MeOH); lit. [ α ] D =+108 ( c =0.14, MeOH), zephycarinatine D: []αD26= +172 ( c =0.15, MeOH); lit.…”
Section: Resultssupporting
confidence: 86%
“…By changing the electrophile to MeI, the total synthesis of zephycarinatine D ( 1 b ) was accomplished in 52 % in three steps with a small amount of removable diene 14 . All the spectroscopic data were in agreement with those of the natural zephycarinatines C and D reported in the literature [2] {zephycarinatine C: []αD26= +141 ( c =0.060, MeOH); lit. [ α ] D =+108 ( c =0.14, MeOH), zephycarinatine D: []αD26= +172 ( c =0.15, MeOH); lit.…”
Section: Resultssupporting
confidence: 86%
“…The chemical structure of these alkaloids was determined by extensive spectroscopic analyses, and absolute configuration of 20 and 21 was confirmed by single crystal X-ray diffraction analysis. Zephycarinatines A ( 74 ), B ( 75 ), and G ( 76 ) represent the first examples of 12-acetylplicamine, N -deformyl- seco -plicamine, and 4a- epi -plicamine alkaloids, respectively [ 69 ]. Narciclasine-4- O- β - d- xylopyranoside ( 51 ), a new narciclasine glycoside, was isolated from the whole plant of Zephyranthes minuta .…”
Section: Occurrence Of Amaryllidaceae Alkaloidsmentioning
confidence: 99%
“…New lycorine derivatives ( 22 ) displayed moderate AChE inhibition (IC 50 = 35.61 ± 1.90 μM) compared to carinatine (IC 50 > 200 μM). The aromatic C-ring in lycorine-sort alkaloids may be essential for their activity against AChE [ 69 ]. Oxoincartine ( 23 ) was inactive against both cholinesterases (AChE and BChE) [ 70 ].…”
Section: Pharmacological Properties Of Novel Amaryllidaceae Alkalomentioning
confidence: 99%
See 1 more Smart Citation
“…The experimental shifts were plotted against the calculated shifts, and least-squares fit lines was confirmed. The calculated shifts for 2a and 2b were corrected by the slope and intercept to get the corrected 13 C shifts ( Table 1 ), and the differences between the corrected and experimental 13 C NMR chemical shifts were analyzed [ 23 , 24 ]. The result showed that the correlation coefficient R 2 of 2a (0.9966) was higher than that of 2b (0.9926) ( Figures S21 and S22 ).…”
Section: Resultsmentioning
confidence: 99%